PENYULUHAN PENYEHATAN MAKANAN DAN MINUMAN BAGI IBU-IBU RUMAH TANGGA RT 03 RW 10 KECAMATAN PASAR REBO DAN PENGURUS CABANG AISYIAH CIRACAS JAKARTA TIMUR - Zulfadewina Zulfadewina; Septi Fitri Meilana; Indah Kusumaningrum (Yayasan Akrab Pekanbaru, 2018)
Food sanitation is an attempt to control the eating factors, people, places and equipment that may or may cause illness or health problems. The food served is not only nutritious and attractive but the quality of washing and drinking tools also plays an important role. Contaminated food and drink will cause various diseases. Food and beverage awareness raising activities for housewives are important as often as possible because of the increasing number of unhealthy foods and beverages due to the use of chemicals to increase consumer interest produced by home or individual industries. Counseling of food and beverage sanitation, so far has touched only a small number of people, whether committed by the institutions concerned or committed by community service activities by universities. From this counsel see that the community desperately needs practical knowledge on how to identify good food and beverages or food and beverages that have been bad for consumption. Keywords: Counseling, Selection, Restructuring of Food and Drink, housewife, Aisyiah branch manager.